2021
DOI: 10.1371/journal.ppat.1009952
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of SARS-CoV-2 with high mortality in mink (Neovison vison) on multiple Utah farms

Abstract: The breadth of animal hosts that are susceptible to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and may serve as reservoirs for continued viral transmission are not known entirely. In August 2020, an outbreak of SARS-CoV-2 occurred on five mink farms in Utah and was associated with high mink mortality (35–55% of adult mink) and rapid viral transmission between animals. The premise and clinical disease information, pathology, molecular characterization, and tissue distribution of virus within i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 48 publications
2
37
0
1
Order By: Relevance
“…Further, it is unlikely that a variant so effective at spreading in the human population would have evolved in a non-human population; as the mutations required to be successful in a human population may well be different due to differences in cell receptors, as well as behaviour. Common mutations appear in animal populations, such as N501T and Y453F in mink across different continents (Eckstrand et al 2021; Lu et al 2021), but are rarely found in human infections, and not in any of the VOCs. While it would be possible for a two-step evolutionary process wherein there is first some adaptation in an animal population, allowing the crossing of a fitness valley, followed by spillover and human adaptation through conventional transmission, it would once again be difficult to explain the intermediate sample we observe through this transmission process.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is unlikely that a variant so effective at spreading in the human population would have evolved in a non-human population; as the mutations required to be successful in a human population may well be different due to differences in cell receptors, as well as behaviour. Common mutations appear in animal populations, such as N501T and Y453F in mink across different continents (Eckstrand et al 2021; Lu et al 2021), but are rarely found in human infections, and not in any of the VOCs. While it would be possible for a two-step evolutionary process wherein there is first some adaptation in an animal population, allowing the crossing of a fitness valley, followed by spillover and human adaptation through conventional transmission, it would once again be difficult to explain the intermediate sample we observe through this transmission process.…”
Section: Discussionmentioning
confidence: 99%
“…The industry is particularly important in Texas where the deer hunting and breeding industry generates over $1.6 billion in economic activity annually ( 16 ). Given the recent findings of wild white-tailed deer infection with SARS-CoV-2, combined with the precedent from mink that captive animal facilities may be high risk transmission environments ( 17 19 ), our objective was to investigate the SARS-CoV-2 exposure and infection status of captive cervids in Texas.…”
Section: Introductionmentioning
confidence: 99%
“…Between April 26 and November 22, 2020, 14 outbreaks of COVID-19 occurred on commercial mink farms in Utah, one outbreak in a commercial mink farm in Wisconsin, and another in Oregon, USA (United States of America). Clinical signs included respiratory signs and sudden death from a total of 12,330 deaths among 145,757 susceptible animals ( Eckstrand et al, 2021 ).…”
Section: Transmissionmentioning
confidence: 99%